The effect of different drying methods on total bioactive properties, individual phenolic compounds, rehydration ability, color, and microstructural characteristics of Asian pear - Kayacan, Selma; Sagdic, Osman; Doymaz, Ibrahim; Karasu, Salih (WILEY, 2022)
This study aimed to investigate the effects of FD (freeze drying), USVD (ultrasound-assisted vacuum drying), HAD (hot air drying). and IRD (infrared drying) methods on drying behavior, total phenolic antioxidant activity, individual phenolic distribution, rehydration capacity, Scanning Electron Microscopy image, and color quality of Asian pear. HAD showed the longest drying period with 420 min and followed by USVD with 345 and IRD with 240 min. The method difference had a significant effect on the total phenolic and antioxidant activity values of the samples (p < 0.05). The TPC, DPPH, and CUPRAC value were found as 111.59-316.40 mg/100 g GAE, 336.94-559.41 mg/100 g TE, and 161.00-859.73 mg/100 g TE, respectively. Samples dried with FD showed the highest TPC and AA values, followed by USVD, IRD, and HAD. The effect of drying techniques on the distribution of phenolic compounds was found to be significant (p < 0.05). HAD and the IRD process caused a decrease in the amount of all identified phenolic compounds. While USVD caused an increase in the amount of Chlorogenic acid, FD did not cause a significant change. Higher HMF results were found in samples dried via IRD followed by HAD. While the porous structure was preserved in the samples dried with FD and USVD, the porosity structure of the samples dried with HAD and IRD completely disappeared. FD and HAD showed the highest and lowest rehydration capacity, respectively. FD and USVD showed lower color change than IRD and HAD. The results of this study showed that USVD and FD can be used as an alternative method to HAD in drying Asian pear. Practical Application Pear fruit is one of the most consumed fruits worldwide. Pear fruit is very sensitive to microbial and enzymatic degradation due to its high sugar, bioactive component, and moisture content. To increase the shelf life of the pear fruit and to ensure consumption throughout the year, it must be subjected to a preservation technique. Drying is one of the main methods used to extend the long shelf life of fruits and vegetables. Undesirable changes may occur in the quality characteristics of fruits during drying. Therefore, determining the appropriate drying method is vital for the quality of the final product. In this study, the effects of different drying methods on many quality characteristics of pear fruit were investigated. This study has the potential to provide a new perspective on the drying of pear fruit.
Keywords: ANTIOXIDANT ACTIVITY; INFRARED RADIATION; HOT-AIR; QUALITY; Food Science & Technology